1983
DOI: 10.1111/j.1476-5381.1983.tb09358.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of transmission in rat sympathetic ganglia by activation of presynaptic α‐ and β‐adrenoceptors

Abstract: 1 Conditions under which transmission in rat isolated superior cervical ganglia may be affected by activation of presynaptic a-and 3-adrenoceptors have been investigated by means of an extracellular recording method. 2 Clonidine caused a small hyperpolarization of the ganglia (mean EC50-2 nM) in unstimulated preparations; with continuous preganglionic stimulation at 0.2 Hz, clonidine markedly decreased the height of the compound action potential (mean EC50-18 nM).3 Phentolamine (0.1 -3 pM) per se increased the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

1984
1984
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
0
8
1
Order By: Relevance
“…Thus, it cannot be excluded that some of the present effects d clonidine have been at a ganglionic level. However, in recent experiments on the superior cervical ganglion of the rat clonidine in supramaximal doses inhibited the compound action potential far less (Medgett 1983) than it reduced the amylase output in the present experiments, suggesting that its major effect in this case is likely to have been at the prejunctional level of the postganglionic neurons. Only receptors belonging to the a2-subgroup seemed to be involved in the response to clonidine, since the mainly a Iadrenoceptor activating agonist phenylephrine (Starke et al 1975b), which has been shown not to cause any amylase secretion from rabbit parotid gland (Asking & Gorjstrup 1980), was without effect on the secretion of amylase caused by sympathetic excitation.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Thus, it cannot be excluded that some of the present effects d clonidine have been at a ganglionic level. However, in recent experiments on the superior cervical ganglion of the rat clonidine in supramaximal doses inhibited the compound action potential far less (Medgett 1983) than it reduced the amylase output in the present experiments, suggesting that its major effect in this case is likely to have been at the prejunctional level of the postganglionic neurons. Only receptors belonging to the a2-subgroup seemed to be involved in the response to clonidine, since the mainly a Iadrenoceptor activating agonist phenylephrine (Starke et al 1975b), which has been shown not to cause any amylase secretion from rabbit parotid gland (Asking & Gorjstrup 1980), was without effect on the secretion of amylase caused by sympathetic excitation.…”
Section: Discussioncontrasting
confidence: 82%
“…However, catecholamines have been shown to depress ganglionic transmission (Marazzi 1939, Lundberg 1952, de Groat & Volle 1966; some of these effects have been attributed to changes in the postsynaptic response (see Libet 1979, see Nishi 19791, and some to a decreased release of acetylcholine from preganglionic nerve endings, as shown in the superior cervical ganglion of the cat (Paton & Thomson 1953) and rabbit (Dawes & Vizi 1973). Whereas the postsynaptic effects seem primarily to have been attributed to dopamine release from SIFcells in the ganglion (Libet & Owman 1974) presynaptic effects in the rabbit and rat have been attributed to a-adrenoceptor activation (Dawes & Vizi 1973, Medgett 1983). Thus, it cannot be excluded that some of the present effects d clonidine have been at a ganglionic level.…”
Section: Discussionmentioning
confidence: 99%
“…4, A and C). ␣ 2 -Adrenoreceptor agonists inhibit excitatory transmitter release in sympathetic ganglia (32). Therefore, as a positive control, we used the agonist of ␣ 2 -adrenoreceptors, UK-14304, 1 M. The amplitudes of fast EPSPs before UK-14304 was added were 26.1 Ϯ 5.3 mV and in the presence of UK-14304 amplitudes were 15.0 Ϯ 4.8 mV, a significant difference (P Ͻ 0.01, t-test, 2-tail, n ϭ 5).…”
Section: Ghsr1a Receptor Agonists Did Not Inhibit Transmission In Symmentioning
confidence: 99%
“…Clonidine has been reported previously to depress transmission in the superior cervical ganglion by an action at &2-adrenoceptors (Brown & Caulfield, 1979;Medgett, 1983). Thus it was of interest to compare depressant potencies of the x2-adrenoceptor agonists at this peripheral site with their potencies for depression of the spinal preparation.…”
Section: Effects On Ganglionic Transmissionmentioning
confidence: 99%